Statewide Clinic Registries: The Michigan Surgical Quality Collaborative - Nikolian, Vahagn C.; Regenbogen, Scott E. (Clinics in Colon and Rectal Surgery, 2019)
Regional clinical registries provide a unique opportunity for shared learning and population-based analyses of the quality of surgical care. Through the “Michigan Model” of pay for participation in strategic Value Partnerships, exemplified by the Michigan Surgical Quality Collaborative (MSQC), the state's dominant private insurer, Blue Cross Blue Shield of Michigan, has sponsored 20 statewide clinical quality improvement collaboratives. MSQC represents a partnership among 73 Michigan hospitals with a robust data infrastructure and flexible platform for the promulgation of best practices in surgical quality improvement. This article will describe the organizational structure of the MSQC, the contributions the registry has made to quality improvement in colorectal surgery, and how future work will align to improve the reliability of improvement-relevant registry data.
Keywords: Regional Collaborative Effort; Michigan Surgical Quality Collaborative; quality improvement; surgical outcomes; process measures; colorectal surgery